Subjectivity associated to the use of rock mass classification in stability analysis of caverns - Sailesh Adhikari; Krishna Kanta Panthi; Chhatra Bahadur Basnet (Scientific Reports)
Abstract Q and RMR systems of rock mass classifications are widely used around the world to characterize rock mass quality and to estimate preliminary rock support for underground structures like tunnels and caverns. Despite being widely used, the ratings given in these classification systems are highly subjective and are based on the judgment of the site engineers and engineering geologists. While carrying out such characterization, parameters associated with each classification system are reported in a range of values instead of a single value. On the other hand, in recent times, Geological Strength Index (GSI) has been used extensively worldwide while carrying out stability assessments of tunnels and caverns. Through this process, the GSI value is linked to different relationships proposed by different scholars. This manuscript aims to demonstrate the sensitivity of the variation of the rock mass quality ratings and their impact on the assessment of the overall stability condition of underground caverns. The in-depth assessment of the deformation condition is analyzed using numerical modelling for different GSI values from the same rock mass class classified by Q-system. For this purpose, an underground powerhouse cavern located in the higher Himalayan region is considered a case project. The powerhouse cavern is characterized by Q-system values ranging from 3 to 40 and GSI values from 44 to 73. Stability assessments are carried out using combinations of numerical, empirical, analytical, and semi-analytical approaches. The analysis indicated that the cavern remains stable, but the results exhibited notable variation due to the sensitivity of GSI as an input to the analyses. Finally, the limitations of the use of GSI in numerical modelling are comprehensively discussed.